Critical Examination of Gender Equality in Responsible Research and Innovation context: A Bibliometric Analysis - Bagočiūnė, Laura (Information & Media, 2024)
Introduction. Responsible Research and Innovation (RRI) is increasingly crucial for addressing societal challenges and promoting sustainable economic growth. While RRI principles have been institutionalized in Europe, gender equality (GE) within this framework remains underexplored. GE policy in the European Union (EU), rooted in gender mainstreaming since 1999, addresses socially constructed roles shaped by intersecting factors like race and class. Recognized as a human right and vital for sustainable development, GE enhances participation, eliminates barriers, and integrates gender perspectives into research. This study examines the integration of GE within the RRI framework to address this gap.Method. A two level bibliometric analysis was conducted using Scopus and Web of Science (WoS) databases, focusing on English-language, open-access articles published between 1985 and 2024. Following the application of exclusion criteria, a total of 2134 documents were analyzed, comprising 2045 in Phase 1 and 89 in Phase 2.Analysis. The analysis revealed a significant underrepresentation of GE within the RRI discourse. Despite a growing interest in RRI, there is a lack of meta-analytical studies focusing on GE, with research predominantly addressing broader aspects of RRI.Results. From the 2134 documents analyzed, only 89 explicitly addressed GE within the RRI context. Co-occurrence networks identified four primary RRI clusters emphasizing sustainability, governance, education and ethics. GE related keywords formed smaller, peripheral clusters, indicating marginal representation. The findings underscore a lack of systemic integration of GE into the broader RRI framework.Conclusions. The study highlights the critical need to prioritize GE within the RRI agenda by embedding it across all its dimensions. Addressing this gap will enhance the inclusivity, societal relevance, and ethical alignment of RRI initiatives. Policymakers and institutional leaders must champion GE as a foundational element of RRI to advance sustainable and equitable innovation.
Keywords: Responsible research and innovation (RRI); Gender equality (GE); bibliometric analysis; VOSviewer